Effects of intermittent fasting on performance and body composition in athletes. Systematic review - Tejada-Medina, Virginia; Domínguez Ramírez, Daniel; Martín-Moya , Ricardo (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The practice of intermittent fasting is a current topic that has been making its way into the dietary landscape in recent years. The purpose of this literature review was to analyse the effects of intermittent fasting in conjunction with physical activity on the performance and body composition of athletes. The search was carried out in the Web of Science and Scopus databases, using the descriptors «intermittent fasting» y «intermittent dietary intake». Of the 246 results initially obtained, 20 met the inclusion criteria and were selected for this study. The articles analysed focus mainly on the use of intermittent fasting and physical exercise to improve performance and body composition. Upon analysis, we found findings consistent with national and international literature regarding the benefits of intermittent fasting. In conclusion, intermittent fasting, together with physical activity, favours the loss of fat mass and, consequently, body weight, as well as improving health-related biomarkers. However, all the scientific literature reviewed suggests the need for further studies to reinforce these conclusions.